Duke and the great pie war - Big Idea Productions (New York, NY : Sony Wonder, 2005)
Based on the story of Ruth and Naomi. When the armies of Rhubarb go to battle against the Kingdom of Scone, the Great Pie War breaks out and things get really messy! Duke and the Great Pie War is an adventure featuring a lesson on loving your family.
Duke and the great pie war -- Baby sitter in DeNile.
Special features: behind the scenes; progression reel; art gallery; jousting documentary; deleted scenes; trivia; karaoke; interactive storybook; obstacle course game; family activity; how to draw Petunia; how to draw Miriam; DVD-ROM fun; hidden Easter eggs; previews.
Cover title: Veggie tales: Duke and the great pie war.
MPAA rating: Not rated.
DVD.
Soundtrack: English; subtitles: English, Spanish.
Animation, DPX Studios ; musical score, Kurt Heinecke.
Keywords: Families -- Juvenile films; Love -- Juvenile films; Animated films; Children's films; Animated films; Children's films; Families; Love; Video recordings for the hearing impaired; Films; Juvenile works